The Experiences of People Living with HIV in Seeking HIV Health Services During Covid-19 Pandemic in Denpasar - I Putu Supardika Wiratama; Nyoman Agus Jagat Raya; I Gusti Ngurah Juniartha (Universitas Jember, 2023)
People living with HIV (PLWH) need to maintain their health status by seeking HIV health services. However, HIV health services have been impacted by the Covid-19 pandemic and affect antiretroviral therapy (ART) for people living with HIV. This study aimed to explore the experiences of people living with HIV in seeking HIV health services during the Covid-19 pandemic. This study used a qualitative research design with a descriptive phenomenological approach. Semi-structured interviews were used on eight participants with a purposive sampling technique. Thematic analysis was used for data analysis in this study. This study found three themes, namely barriers to access to HIV health services during the Covid-19 pandemic, motivation to access HIV health services as the second theme. The third theme is the adaptation of HIV health services during the Covid-19 pandemic. PLWH have challenges accessing HIV health services during the Covid-19 pandemic. However, they have the motivation to maintain their health status by following new policies during the new normal period during the Covid-19 Pandemic. Communication, information, and education related to Covid-19 and new policies in accessing HIV health services must be provided by HIV nurses. The goal of such provision is to maintain health status, prevent lost to follow-up ART, and improve the quality of life of PLWH.